EKSPLORASI ETNOMATEMATIKA PADA UDENG PACUL GOWANG SIDOARJO - Salsabila; Khurotul Mufidah; Agus Prasetyo Kurniawan; Ahmad Lubab (PT Innovative Academic Journals, 2025)
This research explores ethnomathematics in Udeng Pacul Gowang Sidoarjo. The research method used is a qualitative method with an ethnographic approach. The data collection technique used in this research is observation and the data analysis technique used is descriptive analysis. The results of this research prove that there are several mathematical concepts in Udeng Pacul Gowang Sidoarjo which include straight lines, curved lines, flat shapes, and the concept of congruence.